Analytical Tools dan SWOT Analysis Penggunaan M-Banking Perbankan Syariah di Indonesia - Dedy Mainata (Al-Tijary, 2018)
The current shift in banking services is focused in banking technology. Similarly, this is also happening to sharia banking in Indonesia. Banking technology is one of the services that are favored by sharia banking in the competition to attract customers. M-Banking services is one of the products being offered by sharia banking technology, providing the costumer with the highest and newest developments in technology. This goes together with the increasing demand for easier procedures.The significant development of M-Banking services in sharia banking in Indonesia helps evaluating the customers' satisfaction with a specific product. Through M-Banking SWOT analysis, it is expected that the quality of banking services can be improved. This paper aims to analyze more deeply about the strengths, weaknesses, opportunities, and threats (SWOT) of M-Banking services of sharia banking in Indonesia.The strengths of M-Banking banking services are cost-effective, time-saving, attractive features, easy to operate, easy to download, interesting promo, Islamic content info. Weaknesses of M-Banking services in sharia banking are slow data access speed, insufficient Security, network limitations, the lack of accessibility and performance by all customers, and M-Banking functionality still under development process. The outstanding points of M-Banking of sharia banking are the development of performance, functionality and bandwidth of M-Banking server which have the potential to increase the number of customers. In conclusion, main challenges regarding M-Banking are the competition between banks, the relationship between the confidentiality of customer data and its possible misuse by employees or hackers, accessibility, effectiveness and efficiency of the product, as well as improvement of functionalities and performance of M-Banking service.